Sonora: An Autonomous Analyst for Anti-Money Laundering Based on Explainable Artificial Intelligence - Batista, Vlademir Lenin Donato; Castro, Paulo André Lima de (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.12402, 2025)
This paper presents the development and evaluation of Sonora, an autonomous analyst based on explainable artificial intelligence (XAI) designed to support Anti-Money Laundering (AML) monitoring in financial institutions. Using real-world, imbalanced data from a Brazilian financial institution, we developed a predictive model to identify suspicious cases. A multi-stage evaluation process began with the selection of Gradient Boosting as a robust baseline model over other standard classifiers. This model was then benchmarked against an alternative model, XGBoost, selected from a pool of state-of-the-art boosting algorithms. After hyperparameter optimization for both finalists, a threshold-based analysis confirmed that Gradient Boosting delivered the best performance for a recall-focused strategy, achieving a recall of approximately 96%. We deliberately focus on recall rather than accuracy to minimize regulatory risk and ensure that critical cases are surfaced for human review. To foster institutional trust, Sonora integrates instance-level SHAP explanations, highlighting the most influential features in each classification, and it acts as a decision-support tool, not a replacement for human analysts.